2009
DOI: 10.3354/dao01989
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative kidney disease in rainbow trout: time- and temperature-related renal pathology and parasite distribution

Abstract: Proliferative kidney disease is a parasitic infection of salmonid fishes caused by Tetracapsuloides bryosalmonae. The main target organ of the parasite in the fish is the kidney. To investigate the influence of water temperature on the disease in fish, rainbow trout Oncorhynchus mykiss infected with T bryosalmonae were kept at 12 degrees C and 18 degrees C. The number of parasites, the type and degree of lesions in the kidney and the mortality rate was evaluated from infection until full development of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
139
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(142 citation statements)
references
References 27 publications
(20 reference statements)
2
139
1
Order By: Relevance
“…In a recent experimental study dealing with rainbow trout, we showed that as soon as 103 d post-infection no T. bryosalmonae were visible by IHC, independent of water temperature (Schmidt-Posthaus et al 2012). However, translocation into the tubular lumen was not obvious in the latter study, as elimination of T. bryo salmonae seemed rather to be taking place through degeneration of the parasites in the interstitium than by translocation into the tubular lumen (Bettge et al 2009, Schmidt-Posthaus et al 2012. These species differences were also shown by Morris & Adams (2006) and Grabner & El-Matbouli (2008), who were only able to demonstrate excreted spores in brown Salmo trutta and brook trout Salvelinus fontinalis, but not in rainbow trout.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In a recent experimental study dealing with rainbow trout, we showed that as soon as 103 d post-infection no T. bryosalmonae were visible by IHC, independent of water temperature (Schmidt-Posthaus et al 2012). However, translocation into the tubular lumen was not obvious in the latter study, as elimination of T. bryo salmonae seemed rather to be taking place through degeneration of the parasites in the interstitium than by translocation into the tubular lumen (Bettge et al 2009, Schmidt-Posthaus et al 2012. These species differences were also shown by Morris & Adams (2006) and Grabner & El-Matbouli (2008), who were only able to demonstrate excreted spores in brown Salmo trutta and brook trout Salvelinus fontinalis, but not in rainbow trout.…”
Section: Discussionmentioning
confidence: 74%
“…The spread and consequences of the disease are suspected to be enhanced by water temperature (Wahli et al 2008, Bettge et al 2009, Okamura et al 2011). The disease is caused by Tetracapsuloides bryosalmonae (Myxozoa: Malacosporea) (Hedrick et al 1993, Canning et al 2000, with bryozoans as invertebrate hosts (Anderson et al 1999, Longshaw et al 1999) and salmonids as vertebrate hosts (Feist & Bucke 1993, Hedrick et al 1993.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing water temperature is associated with an increasing release of infective spores from bryozoans (Tops et al 2006), which may result in enhanced infection pressure on the fish. At the same time, higher water temperature may promote parasite proliferation in the fish host as suggested by Bettge et al (2009) and Gay et al (2001), and the resulting increase of infection intensity could then lead to the temperaturerelated elevation of mortality. Another aspect is that the fish immune system is modulated by water temperature (Le Morvan et al 1997 ;Köllner and Kotterba, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The main target organ is the kidney (Kent & Hedrick 1985) where T. bryosalmonae undergoes multiplication and differentiation from extrasporogonic to sporogonic stages (Kent & Hedrick 1985). Infected salmonids can excrete spores via the urine (Kent & Hedrick 1985, Morris et al 2002, Hedrick et al 2004, Bettge et al 2009a and transmission of the parasite from fish to bryozoans via excreted spores has been shown for brown trout Salmo trutta and brook trout Salvelinus fontinalis (Morris & Adams 2006, Grabner & El Matbouli 2008.…”
Section: Introductionmentioning
confidence: 99%